2018
DOI: 10.1038/s41598-018-31301-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing reveals key potential long non-coding RNAs related to duration of fertility trait in the uterovaginal junction of egg-laying hens

Abstract: Duration of fertility, (DF) is an important functional trait in poultry production and lncRNAs have emerged as important regulators of various process including fertility. In this study we applied a genome-guided strategy to reconstruct the uterovaginal junction (UVJ) transcriptome of 14 egg-laying birds with long- and short-DF (n = 7); and sought to uncover key lncRNAs related to duration of fertility traits by RNA-sequencing technology. Examination of RNA-seq data revealed a total of 9977 lncRNAs including 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…Thus, we performed histological analysis of UVJ tissue and observed a significant difference in the density of SSTs between the HFSS and LFSS hens. A similar situation was reported by Adetula et al [59], who found more SSTs were embedded in the HFSS hens compared with LFSS hens.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, we performed histological analysis of UVJ tissue and observed a significant difference in the density of SSTs between the HFSS and LFSS hens. A similar situation was reported by Adetula et al [59], who found more SSTs were embedded in the HFSS hens compared with LFSS hens.…”
Section: Discussionsupporting
confidence: 87%
“…Understanding the epigenetic determinants of animal diseases and their role in pathogenesis, control, treatment and eradication represents a major opportunity to apply epigenetic markers for further improvement of animal productivity (Waddington, 2012). Skeletal muscle growth and differentiation (Luo et al, 2013;Nie et al, 2015), milk production (Yang et al, 2018) and egg laying (Adetula et al, 2018) are precisely regulated by hormonal and developmental cues with circRNA prominently serving as a rheostat to balance mRNA expression with noncoding RNA regulation.…”
Section: Production Animals -Animal Protein Sourced From Meat Eggs mentioning
confidence: 99%
“…RNA-seq is a methodology for RNA pro ling based on next-generation sequencing that enables us to measure and compare gene expression patterns at an unprecedented resolution [12]. In recent years, to further explore the molecular mechanisms that regulate important economic traits of poultry, a large number of poultry transcriptome studies have been performed using RNA-Seq [7,[13][14][15][16]. The development of RNA sequencing has provided a powerful, highly reproducible, and cost-e cient tool for exploring the molecular mechanism of traits.…”
Section: Introductionmentioning
confidence: 99%